Historical Review of Mahalaxmi Municipality: An Integrated Development Perspective (Research Nepal Journal of Development Studies, 2018)
The history of Mahalaxmi Municipality is starting from Ramayana era, so it is completely a historical settlement, sets back to the timeline of 5000 BC. Archeology Department of Government of Nepal had explored the place and found the symbols of stone age weapons here in Lubhu. Shringi Rishi, who organized the Putresthi Yagya (Embryological Treatment) to give the birth of Ram Laxman – the God, sons of King Dasharath of Ayodhya, India, was born in Lankuri Bhanjyang of the Municipality. Typical Newari settlements of Lubhu and Siddhipur have unique history and culture – completely different from other Newar of Kathmandu Valley. The most beautiful land like gold of Ganga Maharani is Called Lubhu in Newari. Culturally Buddhists philosophy of  Nalanika  Jatak is also associated with the holy land of Serang or Shringi Rishi. The study is based on personal observation, review of old literatures, and Tourism Master Plan 2017 of the municipality.